Використання мультимедійних технологій при створенні програмно-апаратної системи управління - Храмцов, П. В. (ХНУРЕ, 2023)
This work solves the problem of combining objects with the help of sensors and creating a system for them, capable of transmitting various useful data in real time independently, without requiring constant control by people. This is facilitated by the spread of wireless Internet networks and the development of cheap microprocessors